Lingual Frenectomy as Treatment of Ankyloglossia in Children: A case report - Saskianti, Tania; Aprillia, Zita; Puteri, Mega Moeharyono; Az Zahra, Alivy Aulia; Tedjosasongko, Udijanto (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: Ankyloglossia or tongue tie is a congenital condition that results when the inferior lingual fraenulum is too short and attached to the tip of the tongue, limiting its normal movements. It causes restricted tongue mobility which in turn causes feeding difficulties and speech problems. Purpose : The article was aimed to report the treatment of an eight years old boy who came with the chief complaint of difficulty in moving his tongue freely which causes speech difficulties. Case Management : The patient was treated for a lingual frenectomy procedure under local anaesthesia using one haemostat method. The haemostats were used to delimit the area to be excised as well as to guide the incisions. One haemostat used to clamp the upper aspect of the fraenulum may be helpful to guide the incision close to the ventral surface of the tongue. After the release of the tongue, care must be taken not to injury the submandibular ducts when making the second incision at the lower aspect of the fraenulum. After 1 to 2 weeks the incision was completely healed. Discussion: Ankyloglossia occurs due to failure in cellular degeneration leading to longer anchorage between tongue and floor of the mouth. Surgical intervention for treating ankyloglossia includes conventional technique with hemostats, electrocautery and laser. In this case, patient was undertaken surgical intervention using one hemostat method. Conclusion: The ankyloglossia case showed that the frenectomy gave good healing with no post operative complications in 8 years old boy.